1990
DOI: 10.1104/pp.92.3.837
|View full text |Cite
|
Sign up to set email alerts
|

Interorgan Translocation of 1-Aminocyclopropane-1-Carboxylic Acid and Ethylene Coordinates Senescence in Emasculated Cymbidium Flowers

Abstract: In Cymbidium flowers, emasculation by removal of the pollinia and the anther cap leads within 24 hours to red coloration of the labellum (lip). Lip coloration, being the first sign of senescence in these flowers, has been ascribed to the action of ethylene in the lip. When a small incision in the base of the lip is made prior to emasculation, or when the lip is excised and placed in water within 10 to 15 hours after emasculation, coloration is considerably delayed. This indicates that a coloration-associated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 17 publications
4
35
0
Order By: Relevance
“…The beneficial effect of MCP on flowers with damaged pollinia is highly significant, as this form of damage occurs readily during packing and transport. There has been some debate about the nature of the transmitted signal from wounded flower parts (Woltering 1990a;Woltering et al 1995). Kwack et al (1996) showed that an inhibitor of ethylene production (aminovinylglycine) protected Cymbidium orchids from the effects of damaged pollinia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effect of MCP on flowers with damaged pollinia is highly significant, as this form of damage occurs readily during packing and transport. There has been some debate about the nature of the transmitted signal from wounded flower parts (Woltering 1990a;Woltering et al 1995). Kwack et al (1996) showed that an inhibitor of ethylene production (aminovinylglycine) protected Cymbidium orchids from the effects of damaged pollinia.…”
Section: Resultsmentioning
confidence: 99%
“…The signal which causes accelerated senescence after pollen release is believed to be gaseous ethylene (Burg & Dijkman 1967;Woltering & Somhorst 1990;Woltering et al 1995), but other factors such as 1-aminocyclopropane-l-carboxylic acid (ACC) have been implicated (Woltering 1990a). We describe here the effect of MCP treatment of intact or damaged flowers in the presence or absence of added ethylene.…”
Section: Introductionmentioning
confidence: 99%
“…ACC synthase activity has been reported to be induced in response to emasculation in the gynoecium, but not the perianth, of Cymbidium flowers (Woltering, 1989;Woltering and Somhorst, 1990). Based on results with orchids and other flowers, it has been demonstrated that ACC, synthesized in the gynoecium, is translocated to the perianth where it is converted to ethylene by ACC oxidase (Whitehead et al, 1983Woltering, 1990). Such a spatial separation of ethylene biosynthetic enzyme activities could provide the basis for interorgan coordination of the postpollination syndrome of developmental events.…”
Section: Dlscusslonmentioning
confidence: 99%
“…Emasculation constitutes a physical perturbation that accompanies pollination, whereas ACC and auxin are two substances reported to be a component of orchid pollen (Fitting, 1909;Müller, 1953;Arditti, 1979;Stead, 1992). The role of emasculation as an important signal in the postpollination syndrome was investigated because it has been previously reported that emasculation leads to pigmentation changes, perianth senescence, and the induction of ACC synthase activity in the column, but not the perianth, of Cymbidium orchid flowers (Arditti, 1979;Woltering, 1989Woltering, , 1990Woltering and Harren, 1989;Woltering and Somhorst, 1990). In our experiments, emasculation of flowers detached from the plant resulted in both ethylene production and changes in ACC synthase and ACC oxidase mRNA abundance in most organs.…”
Section: Dlscusslonmentioning
confidence: 99%
“…Ethylene significantly increased stomatal conductance, root hydraulic conductivity (L p ), and root oxygen uptake in hypoxic seedlings. Ethylene can increase plasma membrane permeability permitting more water to cross the cells [106]. At the whole plant level, increased water transport in hypoxic aspen seedlings exposed to ethylene was explained in terms of enhanced aquaporin activity, probably due to a direct effect of ethylene on the phosphorylation of aquaporins [107].…”
Section: Relationships Between Plant Aquaporins and Hormonesmentioning
confidence: 99%